The Role of Jamkeswacht in Helping Cicadas Village Communities Who Experience Health Service Difficulties - Maulidin Rasid, Sugih; Lestari, Nisa (AMK : Abdi Masyarakat UIKA, 2023)
Jamkeswatch is a national social health insurance supervisory institution established by the Confederation of Indonesian Trade Unions as a control function for the implementation of National Health Insurance and the Social Health Security Organizing Agency. This is done to ensure that the implementation of health insurance in this country can run as we expect. In addition to criticizing policies, Jamkeswatch also advocates for people who have difficulty having access to health insurance. In this research, we will discuss the role of Jamkeswatch in helping people who experience difficulties, especially in the Cicadas Village area, Bogor Regency.